Mesoporous Materials Used in Medicine and Environmental Applications - (:unkn) unknown (BENTHAM SCIENCE PUBL LTD, 2015)
Mesoporous materials synthesized in the presence of templates, are commonly used for environment and medical applications. Due to the properties it holds, mesoporous silica nanoparticles is an excellent material for use in medical field, biomaterials, active principles delivery systems, enzyme immobilization and imaging. Their structure allows embedding large and small molecules, DNA adsorption and genetic transfer. Using mesoporous silica nanoparticles for delivery of bioactive molecules can protect them against degradation under physiological conditions, allow controlled drugs release and minimize side effects on healthy tissues. Cellular tests performed on mesoporous silica nanoparticles demonstrate that MSN's cytotoxicity is dependent on the size and concentration and suggests the use of larger size nanoparticles is optimal for medical applications. Mesoporous materials possess high biological compatibility, are non-toxic and can be easily modified by functionalizing the surface or inside the pores by grafting or co-condensation method. The structure, composition and pores size of this material can be optimized during synthesis by varying the stoichiometric reactants, reaction conditions, nature of the template's molecules or by functionalization method.
Keywords: Cancer therapy; Drug delivery; Heavy metals removal; Mesoporous silica; SILICA NANOPARTICLES; DELIVERY-SYSTEM; DRUG-DELIVERY; HEAVY-METAL; CONTROLLED-RELEASE; AQUEOUS-SOLUTIONS; REMOVAL; PHARMACEUTICALS; ADSORPTION; IRON